Altered regulatory T‐cell fractions and Helios expression in clinically isolated syndrome: clues to the development of multiple sclerosis. Issue 5 (26th May 2017) - Jones, Anderson P; Trend, Stephanie; Byrne, Scott N; Fabis‐Pedrini, Marzena J; Geldenhuys, Sian; Nolan, David; Booth, David R; Carroll, William M; Lucas, Robyn M; Kermode, Allan G; Hart, Prue H
Abstract : Development of multiple sclerosis (MS) is frequently preceded by an acute or subacute neurological disturbance referred to as clinically isolated syndrome (CIS). The specific immunological disturbances present in CIS remain underexamined. This study analysed peripheral blood mononuclear cells from n =18 treatment‐naive individuals with recently diagnosed CIS (<120 days) for disturbances in the phenotype of T regulatory (Treg), follicular T regulatory (Tfr), T helper (Th), follicular T helper (Tfh) and B cells. Relative to healthy controls ( n =19), CIS was associated with lower proportions of suppressive CD45RA + FoxP3 lo Treg and Tfr cells and greater proportions of non‐suppressive CD45RA − FoxP3 lo and Th17‐like Treg and Tfr. Lower Helios expression (mean fluorescence intensity) was measured across all Treg and Tfr fractions in the CIS group, suggesting less potent regulatory function. Greater frequencies of activated, efficient B‐cell helper Tfh subsets and a trend for a higher proportion of IgD − CD27 − B cells was also detected in the CIS group, characteristics that were positively correlated with Treg and Tfr Helios expression. These results indicate that Treg and Tfr impairment is an early feature in MS. Neurology: Changes in T cells precede multiple sclerosis: Neurological attacks that commonly precede multiple sclerosis are associated with impairment of the immune system's T cells. A team led by Prue Hart from the Telethon Kids Institute at the University of Western Australia in Perth characterized the immune cells in the blood from 18 people who had been recently diagnosed with clinically isolated syndrome (CIS), a condition that often leads to multiple sclerosis, and 19 healthy controls. Looking at a subpopulation of immune‐modulating cells known as regulatory T cells, the researchers found that patients with CIS had lower levels of the kind that suppress immune responses and higher levels of the kind that induce inflammation. The regulatory T cells also showed molecular signs of dysfunction, as did B cells from CIS patients. The findings highlight several immune aberrations that could be targeted to halt the course of the disease.